Spanish, US and Icelandic adolescents: a comparative study (Journal of Parents and Teachers, 2026)
Drawing on the Fourth World Conference on Women, held in New York on 6 June 1990, this article presents the views of Spanish adolescents regarding the social roles associated with each gender, paying particular attention to the perspectives of adolescent girls in order to explore how women perceive themselves. The research, based on a questionnaire and other materials, has sought to highlight the qualities considered ideal in a woman, whilst also addressing other issues.
Keywords: 4th International Conference on Women; adolescents; social roles